Store Novelty dan Loyalitas Toko: Pengaruh Mediasi Store Design Complexity dan Store Design Pleasure - Raynaldi, Aldwin; Supriharyanti, Elisabeth; Mawasti, Alpi (BIP's JURNAL BISNIS PERSPEKTIF, 2025)
One of the biggest challenges faced by the retail sector in the digital era is maintaining customer loyalty to stores. This study aims to analyze the effect of store novelty on store loyalty, with store design complexity and store design pleasure as mediating variables. The study employed a purposive sampling method, involving 120 respondents who were customers of fashion stores in Surabaya. Data collection was conducted using a questionnaire distributed online via Google Forms. The collected data were analyzed using the Partial Least Square (PLS) technique with the SmartPLS 3.0 application. The results show that store novelty does not have a direct effect on store loyalty; however, it has an indirect effect mediated by store design complexity and store design pleasure. These findings provide significant contributions to the retail management literature, particularly regarding strategies for building and maintaining customer loyalty. From a managerial perspective, the study recommends that store managers focus on innovative designs emphasizing variety and comfort to create a unique and enjoyable shopping experience for customers. Effectively managing engaging and complex store design elements can serve as a powerful strategy to enhance customer loyalty amidst the increasing competition in the retail industry.